Occupational Accident Investigation Which Results in the Amputation of Metal Manufacturing Workers ' Fingers - Sukmandari, Erna Agustin; Pratiwi, Anggit (Promotif : Jurnal Kesehatan Masyarakat, 2020)
Everyone who performs manual handling will be at risk for injury. Injuries are not only caused by the heavy burden that is handled but the light and repetitive work can pose a risk of injury. This research analyses the cause of the work accident on manual handling which resulted in the amputation of the fingers of the hand on the metal manufacturing workers. Research is done qualitatively with case studies. The main informant is a worker who has the iron plate clamping to the injury of the hand and amputation. The supporting informant is the HSE officer of the industry. Data analysis through interactive models with data validation using source triangulation. The main cause of the work accident is because of the movements performed at the time of removal of the piece of iron plates that were performed along with the co-worker manually handling were not coordinated. His fellow informant lifts the plate without giving command, so that the finger position of the main informant is pinned. The injuries experienced by the informant are more severe because the pieces of iron plates that will be lifted are still contained the remaining rough and sharp pieces that are eventually amputated on one of the right hand fingers.